Ocean acidification mediates photosynthetic response to UV radiation and temperature increase in the diatom Phaeodactylum tricornutum - Li, Y.; Gao, K.; Villafane, V. E.; Helbling, E. W.; 李炎 (BIOGEOSCIENCES, 2012)
National Basic Research Program of China [2009CB421207, 2011CB200902]; Program for Changjiang Scholars and Innovative Research Team [IRT0941]; National Natural Science Foundation [40930846, 41120164007]; MOST [S2012GR0290]; Consejo Nacional de Investigaciones Cientificas y Tecnicas-Argentina [PIP 12-201001-00228]; Ministry of Education of China Increasing atmospheric CO2 concentration is responsible for progressive ocean acidification, ocean warming as well as decreased thickness of upper mixing layer (UML), thus exposing phytoplankton cells not only to lower pH and higher temperatures but also to higher levels of solar UV radiation. In order to evaluate the combined effects of ocean acidification, UV radiation and temperature, we used the diatom Phaeodactylum tricornutum as a model organism and examined its physiological performance after grown under two CO2 concentrations (390 and 1000 mu atm) for more than 20 generations. Compared to the ambient CO2 level (390 mu atm), growth at the elevated CO2 concentration increased non-photochemical quenching (NPQ) of cells and partially counteracted the harm to PS II (photosystem II) caused by UV-A and UV-B. Such an effect was less pronounced under increased temperature levels. The ratio of repair to UV-B induced damage decreased with increased NPQ, reflecting induction of NPQ when repair dropped behind the damage, and it was higher under the ocean acidification condition, showing that the increased pCO(2) and lowered pH counteracted UV-B induced harm. As for photosynthetic carbon fixation rate which increased with increasing temperature from 15 to 25 degrees C, the elevated CO2 and temperature levels synergistically interacted to reduce the inhibition caused by UV-B and thus increase the carbon fixation.